The overview installation - an out of body experience. - Soh, Eugene Zhuo Sheng. (2013)
The Overview Installation is an out-of-body experience, achieved through the dislocation of perception when the user sees himself or herself from a third-person perspective using a head mounted display and CCTV. This experience disorientates the user from his or her 'normal' mode of perception, presenting to the user the possibility to rethink basic and habitual activities such as the way he or she navigates space in relation to his or her vision with a new sense of self awareness.